Callitriche fuliginea Lansdown 2022, sp. nov. - Lansdown, Richard V. (Zenodo, 2022)
10. Callitriche fuliginea sp. nov. Type: — NEW GUINEA. MOROBE PROVINCE. Mt. Salawaket, shallow water of boggy pool in alpine grassland, 147º 10’ E, 06º 20’ S, 23 January 1963, T.G. Hartley 11224 (Holotype CANB149567.1!; Isotype, GH 00969870!). Etymology: —Named for the dark brown, almost black fruit. Diagnosis: — C. fuliginea can be distinguished from all other Callitriche species by the fully-formed, lingulate lower leaves which are not fleshy, combined with the blackish mature fruit which are more than 1 mm high and wide. It most closely resembles C. ecarinata Lansdown and Hassemer (2021) from which it can be distinguished by its long lingulate leaves, solitary flowers and the larger blackish fruit. Description: —Stem and leaf scales present. Leaf bases connate. Lingulate leaves 5.0– 12.8 mm long × 1–1.8 mm wide; expanded floating or submerged leaves 2.0– 4.5 mm long × 1.5–4.0 mm wide; venation simple with a few loops outside and occasionally within the secondary veins, petiole 1–7 mm long; leaves of terrestrial plants unknown. Flowers solitary. Bracts caducous, very narrow, 1.3 mm long. Styles erect, persistent 2.0– 3.2 mm long. Filament erect, 1.5–2.3 mm long; anthers 0.3–0.4 mm long × 0.4–0.5 mm wide, number of locules unknown; pollen yellow. Fruit subsessile, not strumose, slightly wider than long, black when mature, 1.2–1.3 mm long × 1.3–1.5 mm wide, unwinged. Illustrations: — Fig. 1j. Recognition: — C.fuliginea can be distinguished from all other Callitriche species in the region except C. antarctica and C. heterophylla by its large unwinged, blackish fruit. C. antarctica differs in its fleshy leaves, compared to those of C. fuliginea of which the leaves are thin and delicate. C. heterophylla typically has smaller and characteristically isodiametric fruit. C. palustris could be considered similar, but at least within the region, always has at least a narrow wing at the top of the fruit. Distribution: —Native. C. fuliginea is endemic to New Guinea, where it is known only from the holotype which was ...